2009
DOI: 10.1097/ccm.0b013e3181926104
|View full text |Cite
|
Sign up to set email alerts
|

Combined neuronal and inducible nitric oxide synthase inhibition in ovine acute lung injury*

Abstract: Objective Acute lung injury (ALI) with subsequent pneumonia and sepsis represents a major cause of morbidity and mortality in thermally injured patients. Production of nitric oxide (NO) by the neuronal and inducible NO synthase (nNOS, iNOS) may be critically involved in the pathophysiology of the disease process at different time points and thus specific inhibition at different times may represent an effective treatment regimen. Design Prospective, controlled, randomized trial. Setting University research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
(58 reference statements)
0
31
0
2
Order By: Relevance
“…Wang LF and his colleagues found that both pulmonary parenchymal cells and inflammatory cells contribute to the increased lung iNOS activity in endotoxemia, pulmonary parenchymal cells contribute to a significantly greater degree [46]. Accumulating evidence suggest that inhibitors of iNOS may be potential therapeutic agents for clinical application in patients with ALI/ARDS because the inflammatory responses and ALI following infusion of LPS are due to the production of NO, free radicals and proinflammatory cytokines through the iNOS system [47][48][49][50]. Here, our finding revealed that naringin significantly reduced LPS-induced increment of iNOS activity.…”
Section: Discussionmentioning
confidence: 96%
“…Wang LF and his colleagues found that both pulmonary parenchymal cells and inflammatory cells contribute to the increased lung iNOS activity in endotoxemia, pulmonary parenchymal cells contribute to a significantly greater degree [46]. Accumulating evidence suggest that inhibitors of iNOS may be potential therapeutic agents for clinical application in patients with ALI/ARDS because the inflammatory responses and ALI following infusion of LPS are due to the production of NO, free radicals and proinflammatory cytokines through the iNOS system [47][48][49][50]. Here, our finding revealed that naringin significantly reduced LPS-induced increment of iNOS activity.…”
Section: Discussionmentioning
confidence: 96%
“…MPO concentrations were evaluated on homogenized whole lungs with a commercially available assay (CytoStore, Calgary, AB, Canada). MPO activity was normalized to lung wet-to-dry weight ratio and reported as units per gram of dry tissue, as previously reported (16).…”
Section: Methodsmentioning
confidence: 99%
“…B-2, Santa Cruz Biotechnology, Santa Cruz, CA), and VEGF (mouse monoclonal VEGF antibody; catalog no. VG-1, Abcam) was measured in lung tissue homogenates using a Western blot protocol, as described previously (16). Blots were quantified by National Institutes of Health IMAGEJ scanning densitometry and normalized to total actin expression.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these studies investigated only a few time points during the initial phase after the onset of infection [12][13][14][15][16]. However, recent experimental evidence suggests that the initial phase may be critical [4,17].…”
Section: Discussionmentioning
confidence: 98%